Optimal Visitation of Base Transciever Station Site: (Case Study of Vodafone Network; New Juabeng Municipality, Eastern Region, Ghana) - Ansah, Isaac (2013)
A thesis submitted to the Institute of Distance Learning, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirement for the award of Master of Science degree in Industrial Mathematics.